Analisis risiko operasional dalam perbankan syariah: Identifikasi, pengukuran, dan strategi mitigasi berbasis prinsip syariah - Attamimi, Inas (Maliki Interdisciplinary Journal, 2026)
This study aims to examine operational risks in the Islamic banking sector using a risk management approach that encompasses identification, measurement, and mitigation in accordance with Sharia principles. The method used in this study is qualitative, involving a literature review of various relevant scientific sources on risk management and Islamic banking. The results of this study reveal that operational risks in Islamic banking stem from failures in internal processes, human errors, weaknesses in technological systems, as well as uncontrollable external factors. Additionally, there is a specific risk characteristic in Islamic banking, namely compliance risk with Sharia principles, which can affect the institution’s reputation and legitimacy. The risk identification process is a critical stage for identifying various risk exposures, which are then measured using standard approaches such as the Basic Indicator Approach (BIA) and the Standardized Approach (SA). Furthermore, risk mitigation efforts are implemented by applying the principle of prudence, strengthening internal control systems, improving workforce quality, diversifying the financing portfolio, and optimizing oversight by the Sharia Supervisory Board. Thus, the implementation of integrated operational risk management that complies with Sharia principles is essential for maintaining stability, enhancing public confidence, and supporting the sustainability of the Islamic banking sector.